Paradigms of Interaction Between Culture and Politics - Morteza Bahrani; Seyed Mohsen Alavi Poor (Taḥqīqāt-i Farhangī-i Īrān)
Political thought as a normative knowledge seeks a good society and the means for its realization. Accordingly, every intellectual paradigm introduces us a social and individual situation which is the best. This model, itself requires a dramatic change in the culture and flourishes it. In another words, there is a necessary relationship between the elements of political thought and the culture in every society. This relationship is twofold, so it is impossible to indicate whether which aspect is the first. So every paradigm feeds some special elements into the current culture of society, while there is it feedback. It is important that political thought goes in search of condition for cultural flourishing which is according whit the criteria of good society. This paper focuses on most important paradigm in political thought history and shows the trend in which indicates the relationships between political thought and culture. This trend looks at human beings as "citizen", then "the individual"; and in the modem era, paradigms of "critical modem", "postmodern", and "communitarian" has a key role in prospering the realm of culture.